Acceptability and perception of COVID-19 vaccines among foreign medical students in China: A cross-sectional study - Arthur, Clement; Dong, Zhen; Abudu, Hermas; Li, MengLu; Munthali, George N. Chidimbah; Zhang, Chunming; Zhang, Sen; Han, Rui; Ogbordjor, Stephen; Dormocara, Amos; Ja, Lina; Zhang, Di; et al. (Frontiers in Public Health, 2023)
Background: The acceptability and perception of COVID-19 vaccination among different social groups have been the subject matter of several studies. However, more is needed about to be known about the medical trainees. This study fills the literature gap to assess the acceptability and perception of the COVID-19 vaccine among foreign medical students in China. Methods: An online cross-sectional survey was conducted from March to April 2022. A data-collecting questionnaire was developed to source the data from the students. Using a shared questionnaire link, the authors passed through key informants in different universities across China to collect the data among medical students. The data collection process was only for foreign medical students in China at the time of the study. We received 386 responses from the respondents comprising 140 females and 246 males. After processing and coding the data, the authors applied two estimation regression techniques, including logistic and multilinear, to evaluate the influencing factors. Results: The results show that 4.9% were less than 20 years, 91.5% were 20-40 years, and 3.6% were above 40 years. Overall, 36.3% of respondents were females, and 63.7% with males. The gender variable shows (β=0.235, p=0.002), suggesting that gender is a significant factor in acceptability and perception in the study. Also, the opinion on the safety of the vaccine reveals (β=0.081, p=0.043), doses of the vaccine to receive (β=0.175, p=0.001), vaccine safety with some side effects (β=0.15, p=0.000), and the possibility of acquiring COVID-19 after vaccination (β=0.062, p=0.040) are all significant factors which influence vaccine acceptability and perception. Also, home continent (β=-0.062, p=0.071) is a negative factor influencing COVID-19 vaccine acceptance. Furthermore, the finding shows that fear-perceptions (n=200), making 51.81%, has affected the respondents. Conclusion: COVID-19 vaccination acceptability and perception among medical students in China is high, most predominately due to their knowledge in medicine composition formulation. Despite widespread acceptance by the general public and private stakeholders, we concluded that vaccination resistance remains a significant factor among medical students and trainees.